Update on infections with Thelazia callipaeda in European wildlife and a report in a red fox, Vulpes vulpes, in Portugal - Ana Filipa Lopes; Mariana Ribeiro Ferreira; Beatriz do Vale; Marlene Santos; Inês Silveira; Sofia Claudino; Manuel Martins; Telma Brida; Luís Figueira; Luís Cardoso; Ana Patrícia Lopes; Ana Cláudia Coelho; et al. (Current Research in Parasitology and Vector-Borne Diseases, 2024)
Thelazia callipaeda, also known as the “oriental eye worm”, is a zoonotic parasitic nematode with a wide range of hosts, particularly wild and domestic carnivores, but also lagomorphs and humans. Currently, ocular thelaziosis presents an expanding distribution range throughout Europe, including Portugal. This study provides an update on T. callipaeda infection reports (30 studies) in European wildlife comprising 54 host-locality records in 10 host species from nine European countries. The prevalence of T. callipaeda varied widely, with ranges from around 1% in red foxes and European hares to almost 50% in red foxes. The lowest mean intensity was 2.7 nematodes/host in European wildcats and the highest was 38.0 nematodes/host in wolves. In addition, a massive infection with T. callipaeda in a juvenile male red fox from eastern-central Portugal is also described, representing the southernmost report in a wild animal in this country. A total of 188 nematodes (139 females and 49 males) were collected from both eyes and were submitted to morphological and molecular characterization. Collected nematodes were morphologically identified as T. callipaeda. Given the endemicity of T. callipaeda in eastern-central Portugal, surveillance system should be implemented to monitor its presence among wild and domestic animals.